Critical roles of CTP synthase N-terminal in cytoophidium assembly - Huang, Y; Wang, J; Ghosh, S; Liu, J (Elsevier, 2017)
Several metabolic enzymes assemble into distinct intracellular structures in prokaryotes and eukaryotes suggesting an important functional role in cell physiology. The CTP-generating enzyme CTP synthase forms long filamentous structures termed cytoophidia in bacteria, yeast, fruit flies and human cells independent of its catalytic activity. However, the amino acid determinants for protein-protein interaction necessary for polymerisation remained unknown. In this study, we systematically analysed the role of the conserved N-terminal of Drosophila CTP synthase in cytoophidium assembly. Our mutational analyses identified three key amino acid residues within this region that play an instructive role in organisation of CTP synthase into a filamentous structure. Co-transfection assays demonstrated formation of heteromeric CTP synthase filaments which is disrupted by protein carrying a mutated N-terminal alanine residue thus revealing a dominant-negative activity. Interestingly, the dominant-negative activity is supressed by the CTP synthase inhibitor DON. Furthermore, we found that the amino acids at the corresponding position in the human protein exhibit similar properties suggesting conservation of their function through evolution. Our data suggest that cytoophidium assembly is a multi-step process involving N-terminal-dependent sequential interactions between correctly folded structural units and provide insights into the assembly of these enigmatic structures.